Risk Factors for Prolonged Mechanical Ventilation After Pulmonary Endarterectomy: 7 Years' Experience From an Experienced Hospital in China - Zhang, Congya; Yang, Lijing; Shi, Sheng; Fang, Zhongrong; Li, Jun; Wang, Guyan (Frontiers in Surgery, 2021)
Background: Prolonged mechanical ventilation (PMV) is common after cardiothoracic surgery, whereas the mechanical ventilation strategy after PEA has not yet been reported. We aim to identify the incidence and risk factors for PMV and the relationship between PMV and short-term outcomes. Methods: We studied a retrospective cohort of 171 who undergoing PEA surgery from 2014 to 2020. Cox regression with restricted cubic splines was performed to identify the cutoff value for PMV. The Least absolute shrinkage and selection operator regression and logistic regressions were applied to identify risk factors for PMV. The impacts of PMV on the short-term outcomes were evaluated. Results: PMV was defined as the duration of mechanical ventilation exceeding 48 hours. Independent risk factors for PMV included female sex, prolonged deep hypothermic circulatory arrest (DHCA) time, increased postoperative blood product use, elevated postoperative total bilirubin levels, increased preoperative pulmonary artery pressure (PAP), and elongated postoperative right ventricular anteroposterior dimension (RVAD). Patients with PMV had longer intensive care unit stays, higher incidences of postoperative complications, and higher in-hospital medical expenses. Conclusions: Female sex, prolonged DHCA time, increased postoperative blood product use, elevated postoperative total bilirubin levels, increased preoperative PAP and elongated postoperative RVAD were independent risk factors for PMV. Identification of risk factors associated with PMV in patients undergoing PEA may facilitate timely diagnosis and re-intervention for some of these modifiable factors to decrease ventilation time and improve patient outcomes.